Cytotoxic activity of simvastatin in T47D breast cancer cell lines and its effect on cyclin D1 expression and apoptosis - Bayu Putra; Mae Sri Hartati Wahyuningsih; Eti Nurwening Sholikhah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Background: Statins (HMG-CoA Inhibitors) is a drug used for decreasing plasma cholesterol levels and used in therapy to prevent coronary artery disease. Research in animals and epidemiological studies showed that statin therapy can decrease risk against cancer associated with cholesterol. Based on that result then research of cytotoxic activity against simvastatin knowing cultur T47D breast cancer cells and his influence in decreasing expression of cyclin D1 and induction of apoptosis has been done.Research objectives: The aims of this research is to prove activities of simvastatin against T47D breast cancer cell culture, especially to examine cytotoxic activity, cyclin D1 expression, and simvastatin effect in apoptotic induction.Research method: The type of this research is quasi experiment with using posttest with non-equivalent control group design. Cytotoxicity test performed on T47D breast cancer cell cultures using MTT assay to determine IC50 values after given simvastatine. Expression of cyclin D1 and apoptosis induction test detected using flow cytometry with antibody monoclonal anti-cyclin D1 and Annexin V-Pi, then analyzed by FACS-Calibur program.Results: Simvastatin has cytotoxic effect against T47D breast cancer cells with IC50 values 25.25 µg/mL. Simvastatin with concentrations of 6.31; 12.62; 25.25 and 50.5 µg/mL was able to decrease the cyclin D1 expression. Furthermore, simvastatin can induce apoptosis with EC50 values 26.96 µg/mL in T47D breast cancer cells.Conclusion: Simvastatin has cytotoxic activity of in T47D breast cancer cells and decreasing cyclin D1 expression and inducing apoptosis activity in T47D breast cancer cells.Keywords: simvastatin, cytotoxic, cyclin D1, apoptotic, T47D.